Effects of Non-Financial Performance Management and Risk Disclosures on Not-For-Profit Financial Vulnerability: Evidence from The Australian Aged Care Not-For-Profit Sector - Deshani C. Hettiarachchi (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Questions- To what extent are NFPs in the Australian aged care sector engage in non-financial performance and risk disclosures in their annual reports? What is the effect of non-financial performance and risk disclosures on the extent of financial vulnerability (FV)? Motivation- Research on measuring and understanding the determinants of FV or financial crisis within the not-for-profit (NFP) sector is both scant and limited. To address these gaps in the literature, the paper investigates the extent to which NFPs in the Australian aged care sector make voluntary disclosures related to non-financial performance management (NFPM) and risk information disclosures and examined the impact of NFPM and risk disclosures on the extent of FV in the Australian aged care NFP sector. Idea- The NFPM and risk information disclosures expected to be negatively associated with FV or financial crisis. Data- Data for the study is taken from publicly available database, the Australian Charities and Not-for-Profit Commission website, and quantitative content analysis was conducted to measure the extent of non-financial disclosures using data collected from the audited annual reports issued by 200 aged care NFPs for the years 2018 and 2019. Tools- The dependent variable of this study is the extent of FV that has been measured using the proposed multi-dimensional FV framework. Descriptive statistics, such as, provides mean, median, standard deviation, maximum and minimum values to recognise nature and extent of NFPM and risk information disclosures. For the inferential statistics, the study analyses the research model using multiple regression analysis. Findings- Panel regression results indicate inadequate disclosures of NFPM, and risk information are associated with the extent of FV of NFPs in the Australian aged care sector. The study identifies that only beneficial reporting, such as NFPM reporting and beneficial risk information, helps reduce the extent of FV in the NFP sector. Contribution- the study provides novel insights into the relationship between voluntary non-financial information disclosures (i.e., disclosures of NFPM and risk information) and the extent of FV in the NFP sector. Moreover, it provides a key contribution from the NFP context by recognising a positive and significant association between voluntary risk information reporting and the extent of FV in the NFP sector.
Keywords: M41; 650; not-for-profit organisations; Australian aged care sector; financial vulnerability; non-financial performance measurement disclosures; risk management disclosures